Transformation of 3D object into flat ribbon for RPS additive manufacturing technology. Issue 2 (20th March 2017) - Shulunov, Vyacheslav
Abstract : Purpose: This study aims to give a description of conformal transformation Cartesian coordinates into spiral coordinates using the example of roll powder sintering (RPS) additive manufacturing (AM) technology. RPS has several advantages over dominant AM processes currently available in the market. RPS allows accomplishing designs, which are impossible, very expensive and difficult to create by other methods. The technology requires slicing a 3D object with spiral scanning. Design/methodology/approach: The paper describes the possibility of accurate 3D object transformation into a flat ribbon by spiral coordinate system. Parameters of conformal transformation are calculated according to the equation of equivalence between ( x, y, z ) and ( l, z ) coordinates. Findings: As numerical examples show, it is possible to convert three-dimensional space to two-dimensional one if you know the thickness of the spatial layer. The proposed methodology can be used for the transformation of 3D computer-aided design models into 2D strip models. Originality/value: In this paper, the author proposes a method of converting Cartesian coordinates into spiral coordinates. Conformal transformation of three-dimensional space to two-dimensional one by use of spiral coordinate system is demonstrated by RPS AM technology, which allows to produce objects with high accuracy.